Domino-Heck Type Reactions of N-Benzoyl-2-Azabicyclo [2.2.1]Hept-5-ene-3-one - Yolacan, Cigdem; Ocal, Nuket; Kaufmann, Dieter E. (SPRINGER, 2009)
The coupling of 2-azabicyclo[2.2.1]hept-5-en-3-one and trimethylsilylacetylene or phenylacetylene under Domino Heck conditions gives compounds 2a-c and 4a-c in moderate yields and cyclopentene derivatives, 3a-c in low yields. The procedure can be of use for the synthesis of alkynyl bicyclic lactams.
Keywords: Alkynyl lactams; Heck reaction; Domino-Heck type reaction; rearrangement; PALLADIUM-CATALYZED REACTIONS; Biochemistry & Molecular Biology; Chemistry